Pemberdayaan Ekonomi Perempuan Melalui Qardl al-Hasan Pada Koperasi Simpan Pinjam Wanita Maju Jaya Kebalanpelang Babat Lamongan - Ahmad Ubaidillah; Misbahul Khoir (JES (Jurnal Ekonomi Syariah), 2021)
Abstract: One of the ways to improve women’s economy is cooperatives. The basic objective of women-oriented cooperatives is to empower Indonesian women to contribute to efforts to improve the economic status and welfare of their families. This effort at the same time strengthens the independence of women so that they have strong bargaining power and can make a large contribution to the improvement of the national economy. The role of the qarḍ al-ḥasan contract in the Maju Jaya Women’s Savings and Loan Cooperative, Kebalanpelang Village, Babat Lamongan towards women’s economic empowerment from women’s businesses to create income to support their family's economy. This research is a qualitative research with an investigative pattern in which data and statements are obtained from the results of direct interaction between the researcher and the object under study and the people at the research site. The sampling technique used was purposive sampling and snowball sampling. The data collection techniques used include observation, documentation, and interviews. The data analysis technique uses the Miles and Huberman model. The results showed that the qarḍ al-ḥasan contract applied in the Maju Jaya Women’s Savings and Loan Cooperative can also improve the quality of women’s economic enterprises for the welfare of women in the village of Kebalanpelang Babat Lamongan. Because with the qarḍ al-ḥasan contract, this is one way to help and ease the burden on women who have businesses in capital problems which aim to increase their business to be better and develop than before, so that by means of increasing their business income they earn them. ownership also automatically increases so that women can help their family’s economy. Keywords: qardl al-hasan; women’s savings and loan cooperatives; income